(untitled) - Susana Loureiro Teixeira; Pedro Filipe Azevedo Moutinho; Ana Catarina Pereira Pinto; Liliana Andreia Neves da Mota (University of Ostrava, 2024)
Aim: To measure the level of emotional intelligence in medical-surgical nursing specialist nurses. Design: A quantitative descriptive cross-sectional study. Methods: Data were collected through a digital form comprising a questionnaire divided into two sections: first - sociodemographic and professional characterization; second - a Portuguese version of the Schutte Emotional Intelligence Scale. The internal consistency of the instrument, measured by Cronbach's alpha (unidimensional), was 0.878. Data were collected between 27 January and 16 March 2023. A non-probability convenience sampling technique was used to enroll the participants. Results: The final sample consisted of 168 medical-surgical nursing specialist nurses. Their mean emotional intelligence score was 105.28 points, with a standard deviation of 10.56 points. The variables academic degree (p = 0.002) and gender (p = 0.035) showed a statistically significant association with the total emotional intelligence score. Conclusion: This study allowed to measure the level of emotional intelligence in medical-surgical nursing specialist nurses, yielding high mean scores. Nevertheless, it is essential to invest in strategies for the acquisition of emotional intelligence skills by professionals with low mean scores.